Rheological and Textural Investigation to Design Film for Packaging from Potato Peel Waste - Olga Mileti; Noemi Baldino; Vittoria Marchio; Francesca R. Lupi; Domenico Gabriele (Gels)
The recovery of potato waste for circular-economy purposes is a growing area of industrial research. This waste, rich in nutrients and potential for reuse, can be a valuable source of starch for packaging applications. Rheology plays a crucial role in characterizing film-forming solutions before casting. In this work, packaging film was prepared from potato waste using rheological information to formulate the film-forming solution. To this aim, rheological measurements were carried out on starch/glycerol-only samples, and the data obtained were used to optimize the formulation from the waste. The polyphenol content of the peels was analyzed, and the resulting films were comprehensively characterized. This included assessments of color, extensibility, Fourier-transform infrared (FT-IR) spectroscopy, surface microscopy, and contact angle. Polyphenol-loaded films, suitable for packaging applications, were developed from potato waste. These films exhibited distinct properties compared to those made with pure starch, including an improved wettability of about 75° for the best sample and a high elastic modulus of about 36 MPa, which reduces the deformability but enhances the resistance against the stress. Through rheological studies, we were able to design films from potato peel waste. These films demonstrated promising mechanical performance.